Odpowiedzi

2010-02-28T19:52:48+01:00
7 + (-6)=1
18 + (-21)=-3
-7 + (-2)=-9
-17 + 15=-2
-80 + 12=-68
24 + (-50)=-26
-29 + (-28)=-57
-73 + 17=-56
16 - 50=-34
27 - (-9)=36
-5 - (-12)=-5+12=7
-48 - (-13)=-48+13=-35
-56 -22=-78
-60 - (-17)=-60+17=-43
28 - 72=-44
- 101 - (-29)=-101+29=-72

proszę ;))
2010-02-28T19:54:41+01:00
A) 7 + (-6) =1
b) 18 + (-21)= -3
c) -7 + (-2)= -9
d) -17 + 15= -2
e) -80 + 12= -68
f) 24 + (-50)= -26
g) -29 + (-28)= -57
h) -73 + 17= -56
i) 16 - 50= -34
j) 27 - (-9)= 27+9=36
k) -5 - (-12)= -5 + 12=7
l) -48 - (-13)= -48 + 13= -35
ł) -56 -22= -78
m) -60 - (-17)= -60 + 17= -43
n) 28 - 72= -44
o) - 101 - (-29)= -101 +29= -72
  • DavX
  • Początkujący
2010-02-28T19:55:18+01:00
7+(-6)=1
18+(-21)=-3
-7+(-2)=-9
-17+15=-2
-80+72=-68
24+(-50)=-26
-29+(-28)-57
-73+17=-56
16-50=-34
27-(-9)=-36
-5-(-12)=7
-48-(-13)=-35
-56-22=-78
-60-(-17)=-43
28-72=-44
-101-(-29)=-72